Analisis Klinis Dispepsia pada Pasien Kolelitiasis: Studi Literatur - Gultom, Dea Debora Romauli; Ramadhian, Muhammad Ricky; Lusina, Septia Eva; Darwis, Iswandi (CV. Jasa Sukses Abadi, 2024)
Cholelithiasis, also known as gallstones, is a health problem that has been increasing in prevalence worldwide. Some patients with cholelithiasis experience dyspepsia, a condition that causes discomfort in the upper digestive tract. This study aims to analyze the clinical relationship between cholelithiasis and dyspepsia based on a literature review. The articles used in this study were collected from scientific sources such as PubMed, Google Scholar, and Science Direct. A descriptive analysis was conducted to identify the prevalence, risk factors, and mechanisms linking cholelithiasis with dyspepsia. The results show that most patients with cholelithiasis and dyspepsia are female. The most frequently reported symptoms are abdominal pain (100%), nausea (69%), and vomiting (27%). Eating fatty foods can make these symptoms worse. While many patients feel better after having cholecystectomy, about 30% still experience dyspepsia even after surgery. This connection may be due to issues with gastrointestinal motility disorders, bile reflux, and other multifactorial causes. However, the relationship between cholelithiasis and dyspepsia remains a subject of debate, requiring further research to uncover its mechanisms and develop more effective diagnostic and therapeutic strategies.